THE EXISTENCE OF RELIGION WITHIN TECHNOLOGICAL PROGRESS IN MODERN SOCIETY - Andika Andika (Al'Adalah, 2022)
Today science and technology are considered to be more prominent than others. Religion is believed to be a guide for life, but in modern life, religion is considered an obstacle to the progress of human civilization. Therefore, this article discusses the suspicion that religion delays the process of modernity, especially modern technology, and questions whether religion is the controller for humans to lead their lives. At the same time, the article examines rationality in taking over reli-giosity in modern life. The result of this study is that religion is not an obstacle to the development of modernity because religion provides space for rationality and encourages the development of science in the modern era. Thus, religion contributes significance and cannot be substituted by anything guiding humans in everyday life. This study concludes that religion makes humans have moral and human values